Power management for desktop computer: A review - Candrawati, Ria (2013)
Computer manufacturers have offered various power saving functions to reduce the power consumption of their products.Yet, this function is not sufficiently used because it reduces user convenience in computer usage.Literature on this topic is fragmented: there are no categories in the literature to characterize this power management for desktop (PMD.To address this gap, this paper provides a review of existing studies on this domain focusing on hardware components.